Optimal Positioning of Vibration Monitoring Instruments and their Impact on Blast-Induced Seismic Influence Results - Stanković, Siniša; Dobrilović, Mario; Škrlec, Vinko (Archives of mining sciences = Archiwum górnictwa, 2019)
The major downside of blasting works is blast vibrations. Extensive research has been done on the subject and many predictors, estimating Peak Particle Velocity (PPV), were published till date. However, they are either site specific or global (unified model regardless of geology) and can give more of a guideline than exact data to use. Moreover, the model itself among other factors highly depends on positioning of vibration monitoring instruments. When fitting of experimental data with best fit curve and 95% confidence line, the equation is valid only for the scaled distance (SD) range used for fitting. Extrapolation outside of this range gives erroneous results. Therefore, using the specific prediction model, to predetermine optimal positioning of vibration monitoring instruments has been verified to be crucial. The results show that vibration monitoring instruments positioned at a predetermined distance from the source of the blast give more reliable data for further calculations than those positioned outside of a calculated range. This paper gives recommendation for vibration monitoring instruments positioning during test blast on any new site, to optimize charge weight per delay for future blasting works without increasing possibility of damaging surrounding structures.